The role of kettlebells in strength and conditioning: A review of the literature - Beardsley, C.; Contreras, B. (Strength and Conditioning Journal, 2014)
Studies support the use of kettlebells for improving power, although evidence for using them to improve strength and aerobic fitness is still equivocal. Studies investigating the biomechanical properties of kettlebell training have been fruitful, and it may be useful for developing sprint running performance and for injury prevention. However, we still do not know the optimal loads for maximizing system and joint power production, how the mechanics, joint moments, and electromyographic activity changes as loads increase during kettlebell swings, nor whether kettlebell training transfers to sports performance.